SISTEM KOMUNIKASI PEMASARAN DALAM UPAYA MENINGKATKAN PENGGUNA WISATA NAYA MATAHORA ISLAND RESORT DI KECAMATAN WANGI-WANGI KABUPATEN WAKATOBI - R. Risnawati; Sjamsu Alam Lawelle; Akhmad Mansyur (UNIVERSITAS HALU OLEO, 2022)
This study aims to determine the marketing communication system in an effort to increase tourism users of Naya Matahora Island Resort in Wangi-Wangi District, Wakatobi Regency. This research was conducted at Naya Matahora Island Resort in January - February 2021. Data collection was done by interview, observation, documentation and literature study. The method used in determining respondents is purposive and accidental sampling. The number of samples was 16 people, consisting of 1 tourist manager, 10 tourist users and 5 prospective tourist users. The analysis used is descriptive qualitative analysis. The results of the study concluded that the communication system used to market Naya Matahora Island Resort tourism was by utilizing a marketing mix such as advertising through social media (instagram) and brochures offered to government agencies, sales promotion by providing promo prices and direct selling. However, the promotional communication system carried out through social media is less than optimal so it does not affect the increase in tourist users. The increase in the number of users from 155 people to 534 people was dominated by local tourism users who were only interested in using the swimming pool and enjoying food at the Naya Matahora restaurant. To increase tourism users, the manager should promote their tourism using social media, so that tourism marketing can reach a wider market. Keywords : Naya Matahora, Marketing Communication System, Promotion